Students’ Soft Skills and Their Readiness Towards Industrial Revolution in Technical and Vocational Education and Training (TVET): A Malaysian Sight - Hashim, Suhaizal (Online Journal for TVET Practitioners, 2024)
Industrial Revolution 4.0 (IR4.0) has created massive uncertainty, where the human workforce will be replaced by automation and robotics. Regarding this matter, every Technical and Vocational Education and Training (TVET) student was required to acquire both technical skills and soft skills to sustain their career in a future working environment. Unfortunately, students faced the issue of lacking soft skills, which would have an impact on their readiness to face IR4.0. Thus, this study was conducted to assess the level of TVET students' soft skills and their readiness level to thrive in the industrial revolution, as well as to determine the relationship between the two variables, which are soft skills and readiness to thrive in the industrial revolution. Based on the results, showed that the students in this TVET institution had good soft skills and a moderate level of readiness to thrive in the industrial revolution. The results are also shown that there is a moderately strong relationship between soft skills among TVET students in this TVET institution with their readiness to thrive in the industrial revolution, r (127) = .561, p = .000. The results of the study prove that the student's level of readiness to face IR4.0 are influenced by the acquisition of soft skills, as having soft skills would affect the students' enthusiasm to be ready for IR4.0 adoption.